2016
DOI: 10.1155/2016/3794284
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Relapse Presenting as Complete Monocular Vision Loss due to Optic Nerve Involvement

Abstract: Acute myeloid leukemia (AML) involvement of the central nervous system is relatively rare, and detection of leptomeningeal disease typically occurs only after a patient presents with neurological symptoms. The case herein describes a 48-year-old man with relapsed/refractory AML of the mixed lineage leukemia rearrangement subtype, who presents with monocular vision loss due to leukemic eye infiltration. MRI revealed right optic nerve sheath enhancement and restricted diffusion concerning for nerve ischemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Patel reported a patient with AML relapse who similarly presented with visual loss. MRI of the brain and orbits showed enhancement in the optic nerve, trigeminal nerve and cerebellum 1…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patel reported a patient with AML relapse who similarly presented with visual loss. MRI of the brain and orbits showed enhancement in the optic nerve, trigeminal nerve and cerebellum 1…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukaemia (AML) is cancer of the myeloid lineage of the blood cells where there is over production of abnormal myeloblasts 1…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published treatments typically consist of chemotherapy, steroid administration, localized radiation, or a combination thereof. [7][8][9][10] One report of using radiation alone was shown to be effective in bringing the infiltration to regression and regaining vision, but this case was isolated to the optic nerve head and a 1-year time course was reported for complete recovery. 8 Another report showed that Dasatinib alone can also be effective in treating optic nerve infiltration in a Philadelphia chromosome positive patient.…”
mentioning
confidence: 99%